Analysis of D-Dimer Level and Prothombin Time (PT) Activated Prothombin Thromboplastin (APTT) on Heparin Administration to COVID-19 Patients - Yorike, Dela; Kurniawan, Muhammad Rizki; Syafaat, Mohamad (Universitas Nahdlatul Ulama Surabaya, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Coronavirus is a dangerous pathogen that affects both humans and animals. Symptoms and indicators of COVID-19 infection include fever, cough, and shortness of breath, which are common in respiratory illnesses. COVID-19 has spread globally with high mortality and morbidity rates. Prothrombin Time (PT), Activated Prothrombin Thromboplastin (APTT), and D-Dimer parameters are blood tests to evaluate the coagulation status of COVID-19 patients, all these parameters increased in COVID-19 patients. This study aims at determininig the levels of D-Dimer, PT, and APTT in COVID-19 patients. Clinical and laboratory records were retrospectively reviewed from 100 cases of COVID-19 admitted to hospitals. This study used a a cross-sectional, descriptive, secondary data analysis design. The sample included patients from the Bhayangkara TK. I R.Said Sukanto Hospital between April-July 2021. The sample is a COVID-19 patient who was treated in the Intensive Care Unit (ICU), worsened, and given heparin. An independent variable is the administration of intravenous heparin at prophylactic doses. Dependent variables are D-Dimer, PT, and APTT values. The collected data is processed using Microsoft Office Excel and then being analyzed. D-Dimer, PT, and APTT levels in COVID-19 patients were initially high or increased after heparin administration decreased or became normal. In conclusion, there was a decrease in D-dimer levels, PT values, and APTT after administration of intravenous heparin at prophylactic doses.